Implication of Climatic Change on Sustainable Environmental and Natural Resource Management in Africa: Individual and Collective Responsibility - Okemasisi, Kinikonda (Machakos University Press, 2021)
The impact of climate change is quite evident: Increasing aridity, disruption of livelihood in term of food and drinking water supply, risking the collapse of marine eco-systems, food insecurity, Arctic melting, loss of glaciers, Amazon and Siberian fires, droughts and floods. Several studies analyzing the content of scientific articles on climate show that almost all articles that take a position on the causes of global warming support the scientific consensus that global warming is due to human activity. This is explained first of all by the use of fossil fuels, and secondly by the balance of emissions from changes in land use. The ocean has absorbed about 30% of human made carbon dioxide emissions which has led to acidification of the waters. Global warming relies mainly on the greenhouse gas emissions, which are currently increasing. There is need to redesign our curricula and demand that ecology be at the Centre for the curriculum today at all educational levels; young people need to be taught about the urgency, severity and scientific basis of the climate crisis. Unless we make a paradigm shift in our curriculum design and development and also change our lifestyle, we risk suffering the worst impact of climatic change aforementioned. The paper is a review of both theoretical and empirical studies on impact of climate change in Africa. It brings to the limelight the global views of this impact in Africa. The paper contributes to new knowledge by suggesting the need for the African nations to collectively take responsibility to address the impact of climate change by recommending a Pan African Ecological Curriculum.
Keywords: Impact of climate change; Pan African Curriculum; African Nations; Collective Responsibility